Enrichment of C5a-C5aR axis predicts poor postoperative prognosis of patients with clear cell renal cell carcinoma - Xi, Wei (Oncotarget, 2016)
Anaphylatoxin C5a and its receptor C5aR on cancer cells constitute a vital axis to cancer progression. In this study, we measured C5aR level by immunohistochemistry in the same cohort of our previous C5a research, and C5a-C5aR axis status was determined by synthesizing C5a and C5aR data. C5aR was an adverse independent prognostic factor for ccRCC patients. Kaplan-Meier analyses revealed the unique position of both C5a and C5aR high population in postoperative survival, based on which patients were then shunted into C5a-C5aR enriched and non-enriched groups. Obviously, C5a-C5aR enriched patients significantly had a poorer overall survival (OS) and recurrence free survival (RFS) compared with non-enriched ones, and the independence of C5a-C5aR axis was verified by multivariable analyses (HR 2.118, P = 0.001 for OS, HR 1.715, P = 0.035 for RFS). Established nomograms based on our findings reflected much better predicting accuracy in contrast with most common used TNM and Fuhrman systems. Meanwhile, consistent with HR, C5a-C5aR axis in this study held its advantages over C5a and C5aR for OS prediction by c-index analyses, rather than RFS prediction.